“THE CZECH QUESTION” ON THE PAGES OF THE ALMANAC “RUSSKAYA MYSL” AT THE END OF THE XIX-th – THE BEGINNING OF THE XX-th CENTURIES - Igor Vladimirovich Kryuchkov (Вестник Северо-Кавказского федерального университета)
The attitude of the leading Russian almanac “Russkaya mysl” towards the features of development of na-tional revival is considered in this article.